2001
DOI: 10.1128/jb.183.21.6394-6403.2001
|View full text |Cite
|
Sign up to set email alerts
|

Homologues of Neisserial Heme Oxygenase in Gram-Negative Bacteria: Degradation of Heme by the Product of the pigA Gene of Pseudomonas aeruginosa

Abstract: The oxidative cleavage of heme to release iron is a mechanism by which some bacterial pathogens can utilize heme as an iron source. The pigA gene of Pseudomonas aeruginosa is shown to encode a heme oxygenase protein, which was identified in the genome sequence by its significant homology (37%) with HemO of Neisseria meningitidis. When the gene encoding the neisserial heme oxygenase, hemO, was replaced with pigA, we demonstrated that pigA could functionally replace hemO and allow for heme utilization by neisser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
305
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(314 citation statements)
references
References 40 publications
6
305
0
3
Order By: Relevance
“…The relative values for the pKs for the two complexes are consistent with, but not proof for, stronger H-bond stabilization of the ligated OH -by proton donation by a non-ligated water in PaHO than NmHO (see Figure 1C). At this time, the 13 Inspection of Table 1 shows that, while δ DSS (obs) differs by as much as 1.6 ppm between the two complexes, correction for δ dip (calc) for each complex reduces the difference in δ DSS (dia*) to well under 0.2 ppm for all but a few labile protons. Hence the strength of the majority of the H-bonds is strongly conserved upon deprotonating the axial water.…”
Section: Thermodynamics/dynamics Of the H 2 O ⇔ Oh -Transitionmentioning
confidence: 96%
See 1 more Smart Citation
“…The relative values for the pKs for the two complexes are consistent with, but not proof for, stronger H-bond stabilization of the ligated OH -by proton donation by a non-ligated water in PaHO than NmHO (see Figure 1C). At this time, the 13 Inspection of Table 1 shows that, while δ DSS (obs) differs by as much as 1.6 ppm between the two complexes, correction for δ dip (calc) for each complex reduces the difference in δ DSS (dia*) to well under 0.2 ppm for all but a few labile protons. Hence the strength of the majority of the H-bonds is strongly conserved upon deprotonating the axial water.…”
Section: Thermodynamics/dynamics Of the H 2 O ⇔ Oh -Transitionmentioning
confidence: 96%
“…Integration of a high-spin and low-spin resolved methyl peak indicate that 1:1 population occurs at pH 9. 13 C contact shift pattern of the PH substrate. The significant difference in the pKs for the acid-alkaline transition in PaHO and NmHO complexes would allow for significant differences in the effective axial field strength of the OH -ligand, such that different orbital ground states could, in principle, be populated for the two complexes.…”
Section: Thermodynamics/dynamics Of the H 2 O ⇔ Oh -Transitionmentioning
confidence: 99%
“…HO also is present in some pathogenic bacteria such as Corynebacterium diphtheriae, Neisseriae meningitidis, and Pseudomonas aeruginosa (11)(12)(13)(14)(15). In bacteria, heme oxygenase is a soluble cytoplasmic protein, which takes part in the mining of iron from host heme.…”
mentioning
confidence: 99%
“…In a series of in vitro studies we have shown that the cytoplasmic heme-binding protein PhuS forms a specific protein complex with the ironregulated heme oxygenase, HemO (7)(8)(9). Heme is transferred to HemO for further degradation with the release of iron, CO, and biliverdin IX (BVIX) ␦-and ␤-isomers (10,11). P. aeruginosa encodes a second non-iron-regulated heme oxygenase, BphO directly upstream of the phytochrome two-component sensor kinase, BphP (12,13).…”
mentioning
confidence: 99%